2022
DOI: 10.21037/qims-21-477
|View full text |Cite
|
Sign up to set email alerts
|

Virtual monoenergetic images from dual-energy CT: systematic assessment of task-based image quality performance

Abstract: Background: To compare task-based image quality (TB-IQ) among virtual monoenergetic images (VMI) and linear-blended images (LBI) from dual-energy CT as a function of contrast task, radiation dose, size, and lesion diameter.Methods: A TB-IQ phantom (Mercury Phantom 4.0, Sun Nuclear Corporation) was imaged on a thirdgeneration dual-source dual-energy CT with 100/Sn150 kVp at three volume CT dose levels (5, 10, 15 mGy).Three size sections (diameters 16, 26, 36 cm) with subsections for image noise and spatial reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 41 publications
4
17
2
Order By: Relevance
“…The TTF outcomes on these two inserts showed that TTF was weakly influenced by the energy levels on the VMIs. This behavior is different from that usually found in the literature where the TTF decreases as the keV increases from 40 to 70 keV 11,29,30 . However, in these studies, the TTF was calculated with the imQuest software on a low contrast insert (acrylic or polyethylene inserts).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The TTF outcomes on these two inserts showed that TTF was weakly influenced by the energy levels on the VMIs. This behavior is different from that usually found in the literature where the TTF decreases as the keV increases from 40 to 70 keV 11,29,30 . However, in these studies, the TTF was calculated with the imQuest software on a low contrast insert (acrylic or polyethylene inserts).…”
Section: Discussioncontrasting
confidence: 69%
“…This behavior is different from that usually found in the literature where the TTF decreases as the keV increases from 40 to 70 keV. 11,29,30 However, in these studies, the TTF was calculated with the imQuest software on a low contrast insert (acrylic or polyethylene inserts). The low keV noise conditions and the low contrast of these inserts led to a relatively low CNR (CNR < 15).…”
Section: Discussioncontrasting
confidence: 64%
“…[20][21][22] In addition, the routine clinical use of VMIs combined with iterative reconstruction from EID-CT has been limited because of their altered image impression, particularly their blotchier noise texture at low-keV levels. [23][24][25] Virtual monoenergetic images from PCD-CT combined with QIR might offer an improvement in image perception as QIR aims to replicate the noise texture of traditional filtered back projection. Moreover, based on the improved noise properties and the perfect anatomic acquisition registration, PCD-CT has the potential to improve focal liver lesion detection.…”
mentioning
confidence: 99%
“…Former studies have shown the benefits of VMIs and iterative reconstruction for energy-integrating detector CT (EID-CT) with regard to image quality, lesion conspicuity, and diagnostic confidence for liver lesions, 15–19 but some studies reported that these improvements in image quality with iterative reconstruction did not necessarily translate into increased overall diagnostic accuracy 20–22 . In addition, the routine clinical use of VMIs combined with iterative reconstruction from EID-CT has been limited because of their altered image impression, particularly their blotchier noise texture at low-keV levels 23–25 . Virtual monoenergetic images from PCD-CT combined with QIR might offer an improvement in image perception as QIR aims to replicate the noise texture of traditional filtered back projection.…”
mentioning
confidence: 99%
“…However, this methodology has been accepted by multiple researchers who studied on d' of liver lesion in CT based on acrylic insert in image quality phantom. [17][18][19][20] To the knowledge from this study that the d' of low keV VMI is inferior to that from the low-kVp SECT acquisition, the further study should be conducted to study the impact of DECT parameters on d' that may help to improve the d' on VMI images in the future. The phantom study included more clinical lesions is required to add more information relevant to our results.…”
Section: Detectability Index (D')mentioning
confidence: 97%